Editorial: Special Issue on «Advanced Computing: from Theory to Practice» - Tchernykh, A.N.; Hadjali, A. (Trudy Instituta sistemnogo programmirovaniâ, 2019)
This special issue contains selected papers that had been submitted to Proceedings of the Institute for System Programming of the Russian Academy of Sciences. Thirteen submissions from nine countries (England, Mexico, China, Uruguay, Spain, Pakistan, Cuba, Dominican Republic, and Russia) cover several important topics in rapidly expanding area of research and development related with Advanced Computing. Authors show a spectrum of approaches to solve complex problems such as: data-oriented scheduling, scientific workflows, cloud computing, evolutionary algorithms, content distribution networks, soft computing, parallel programming model for multicore machines, high performance computing, data mining, software birth-marking, anomaly detection, swarm robotics, neural networks, machine learning, security, secret-sharing schemes, heterogeneous distributed computing, and Internet of Things.